Design of rGO-BN hybrids for enhanced thermal management properties of polyurethane composites fabricated by 3D printing. (18th August 2022) - Wang, Shuzhan; He, Hui; Ye, Xun; Chen, Rubin; Li, Qunyang; Huang, Bai
Abstract: With the advent of the 5G era, the research and development of efficient thermal management materials has become more and more urgent. Here, a novel reduced graphene oxide-boron nitride (rGO-BN) hybrid was first designed and fabricated by Michael addition and Schiff base reaction, and then its orientation in thermoplastic polyurethane (TPU) matrix was regulated by fused deposition modeling (FDM) 3D printing technology to prepare an efficient polymer-based thermal management material. The results indicated that the preparation of rGO-BN hybrids enabled the synergistic thermal conductivity effect of rGO and BN to be fully exerted. Moreover, the orientation of the filler could be effectively controlled by flexibly regulating the FDM printing methods, thereby promoting the construction of efficient heat conduction paths. Finally, the thermal conductivity of TPU composites reached 2.61 W m −1 K −1, which was 1022% higher than that of pure TPU. In addition, the composite also maintained excellent electrical insulation performance, which further guaranteed its thermal management applications in electronic devices. This work provides a new idea for the design of efficient thermal conductive composites, and further expands the application of 3D printing technology in the field of functional composites. Graphical abstract: Image 1 Highlights: A novel rGO-BN hybrid was first designed and prepared. The preparation of rGO-BN effectively reduced the interfacial thermal resistance. TPU/rGO-BN composites with high thermal conductivity were prepared by FDM 3D printing. The TPU composite also had good thermal stability and electrical insulation properties.